Performance of epoxy-based self-healing mortar - Ariffin, Nur Farhayu (2016)
Concrete is one of the oldest and versatile construction materials. After water, it is the most utilised material in the world. However, due to various reasons, the formation of micro-cracks can lead to a major problem such as corrosion of steel reinforcement and further deterioration of the structure. The cost of repairing deteriorated concrete structures is expensive as effective remedial requires special repair materials and skilled labours. Thus, the development of new technologies and material that can automatically repair cracks, consequently restore or even increase the strength of both mortar and concrete to prolong the service life is highly needed. Nowadays, the self-healing by using bacteria as a healing agent had gained interest among researchers. However, limited study had been conducted on the use of polymer as a healing agent. Thus, the aim of this study is to investigate the effects and behaviour of epoxy resin without hardener as a self-healing agent in mortar. The epoxy resin was used without hardener based on the understanding that it can harden inside the mortar through the reaction between the epoxy resin and hydroxyl ions produced from the cement hydration process. In this study, the mortar specimens were prepared with mass ratio of 1:3 (cement: fine aggregates), water-cement ratio of 0.48 and 5% to 20% epoxy resin of cement content. Two types of curing regimes were used namely dry-curing and wet-dry curing. Normal mortar was also prepared as a control sample. Various tests were carried out to determine the characteristics of materials including viscosity, Fourier transform infrared spectroscopy, X-ray fluorescence and sieve analysis. The performance of the hardened mortar containing epoxy resin without hardener was determined through compressive strength, flexural strength, splitting tensile strength, initial surface absorption, water absorption, apparent porosity, drying shrinkage and strength development. Furthermore, various techniques including X-ray diffraction, scanning electron microscopy and thermogravimetric analysis were used to study the microstructure of the hardened epoxy-modified mortar. The ultrasonic pulse velocity, permeability, damage degree and healing efficiency were conducted to determine the crack healing process by the epoxy resin inside the cracked mortar specimens. The experimental results show that the optimum percentage of epoxy resin used in the mix was 10% as it gives the highest engineering properties compare to other percentage. The wet-dry curing regime was found to give better performance of the sample containing epoxy resin compared to dry curing. The epoxy resin without hardener as a healing agent was found to perform effectively as the compressive strength, ultrasonic pulse velocity and permeability of the cracked mortar samples regain the initial reading with prolonged curing time. The microstructure study also revealed that the epoxy resin reacts with the hydroxyl ions to heal the micro-cracks in the mortar specimen. Overall test results together with microstructure study showed that epoxy resin without hardener can be used as a self-healing agent in repairing the micro-cracks.